DESIGN OF MOBILE AND FUNCTIONAL PHOTOBIOREACTOR - Uysal, Ö; Ekinci, K (MATTER: International Journal of Science and Technology, 2019)
Recently, microalgae are used in sectors such as agriculture, food, cosmetics, animal feed, energy. Raceways are used for the most common open systems for high density cultivation when tubular photobioreactors are used for closed systems. In two decades, there have been significant developments in different photobioreactor designs for commercial scale production of alternative species in the production of commercial microalgae. There is no risk of contamination as a result of controlled cultivation in tubular photobioreactors. This allows intensive and pure cultivation.In this study, 75 x 69 mm acrylic pipes were used for the tubular photobioreactor. Each flow path is set to 2 m. By using a 40 liter closed-loop unit while the total volume of acrylic pipes is 60 liters, total volume is designed as 100 lt. In this photobioreactor designed and prototyped, suitable conditions were established for the cultivation of different microalgae strains. The tubular photobioreactor is made mobile and functional. In this photobioreactor, pH, optical density, biomass values are controlled.As a result, a mobile and functional photobioreactor has been designed to enable the cultivation of different microalgae strains for different sectors for microalgae growing. This photobioreactor is suitable for continuous, semi-continuous and continuous production.